Analysis of Drug Classification using Mechanism of Action. Issue 1 (May 2021) - Puneeth, G R; Mahesh, S R; Adithya, H; Bhargava, Sharma J; Kumari, H A Chaya; Gururaj, H L; Hong, Lin
Abstract: Mechanism of action (MOA) refers to the specific biochemical interaction through which a drug substance produces its pharmacological effect. A mechanism of action usually includes mention of the specific molecular targets to which the drug binds, such as an enzyme or receptor. Receptor sites have specific affinities for drugs based on the chemical structure of the drug, as well as the specific action that occurs there. Drugs usually work by binding to a receptor and up-regulating (agonist) or down-regulating (antagonist) the production of some downstream cellular activity. If it is known that a disease affects some particular receptor or downstream set of cell activity, then scientists can develop drugs faster if they can predict how cells and genes affect various receptor sites. This paper contains a detailed review on Mechanism of Action.